Interaksi Sosial Siswa pada Ekstrakurikuler Pramuka di SMA Negeri 2 Padang Panjang - Dasril Dasril; Wirdatul Aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the achievements reached on the scout activities by the students of SMA Negeri 2 Padang Panjang. Perhaps, one of the factors is caused by social interaction done by the students. This study is aimed to describe the students social interaction viewed from Students’ cooperation in Boy Scouts, Students’ competition in Boy Scouts, and Students’ accommodation in Boy Scout at Scout Extracurricular Activities at SMA Negeri 2 Padang panjang. This research is quantitative descriptive design. The population of this study is the students who follow the scout numbered 40 students. Sample is 50%, that is about 20 students. This study uses stratified random sampling. Technique data collection of this research is questionnaires, with a sheet of questionnaire data collection (questionnaire). Technique of data anlysis is the formula percentage. The result of this research found that (1) students’ cooperation in Boy Scouts in SMA Negeri 2 Padang Panjang is categorized is good, (2) students’ competition in Boy Scouts at SMA Negeri 2 Padang Panjang is categorized is good, and (3) students’ accommodation in scout is categorized is good.Keywords: Social Interaction, Scout Extracurricular